2017
DOI: 10.4103/jispcd.jispcd_326_16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of a primary preventive dental health education programme implemented through school teachers for primary school children in Mysore city

Abstract: Aims and Objectives:The present study was conducted with the aim of evaluating the effectiveness of a Primary Preventive Dental Health Education Programme conducted for 6–12-year-old primary school children in Mysore City.Materials and Methods:A total of 12 schools, one each in the category of Government, Aided, and Unaided, were randomly selected per zone viz., North, South, East, and West. These 12 schools constituted the study group where the Primary Preventive School Dental Health Education Programme (PPSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 14 publications
3
41
0
5
Order By: Relevance
“…Results of our study indicated that attitude scores significantly increased in the experimental group after the intervention compared to the control group. Consistent with our findings, the improvement of attitude for the OH was also seen in other studies in similar settings including Bangladesh [57] and India [58]. Previous research indicated an increase or improvement in action planning for OH as key to achieving optimal behavior in the field of OH [59].…”
Section: Discussionsupporting
confidence: 92%
“…Results of our study indicated that attitude scores significantly increased in the experimental group after the intervention compared to the control group. Consistent with our findings, the improvement of attitude for the OH was also seen in other studies in similar settings including Bangladesh [57] and India [58]. Previous research indicated an increase or improvement in action planning for OH as key to achieving optimal behavior in the field of OH [59].…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance with certain studies conducted by Kay and Locker,[ 9 ] Pakhomov GN et al . [ 10 ] The results of the present study are also in accordance with the study conducted by Naidu and Nandlal,[ 11 ] which also supports the implementation of such programs in schools.…”
Section: Discussionsupporting
confidence: 91%
“…Ağız sağlığı eğitiminde öğretmenlerin etkinliklerinin değerlendirildiği bir çalışmada, 6-12 yaş okul çocuklarının bilgi seviyesi ve ağız hijyeni gelişiminde istatistiksel olarak anlamlı bir artış, plak sevilerinde bir azalma gözlendiği, bununla birlikte bu gelişmenin okula yeni başlayan küçük yaş grubunda çok daha az olduğu bildirilmiştir. 25 Yapılan çalışmada eğitim sonrası kontrol grubunda ağız hijyeninde istatistiksel olarak anlamlı olmayan bir düzelme gözlenirken, plak seviyesi benzer olarak bulunmuştur. Öğretmenlerin eğitim verdiği çocuklarda da benzer sonuçlar elde edilmesi, eğitimin görsel, işitsel ve uygulamalı olması ve tekrarlanarak yapılması durumunda dahi küçük yaş grubunda yeterli olmadığını düşündürmektedir.…”
Section: Tartiġmaunclassified
“…Naidu ve ark., eğitimden 6 ay sonra df-t ve DMF-T indeks değerlerinde düşme saptadıklarını ifade etmişlerdir. 25 Yapılan çalışmada 3 ay sonra def-t, def-s, DMF-T ve DMF-S indeks değerlerinde istatistiksel olarak anlamlı bir fark gözlenmemiştir.…”
Section: Tartiġmaunclassified
See 1 more Smart Citation